Do basic auscultation skills need to be resuscitated? A new strategy for improving competency among nursing students. (February 2021) - Goldsworthy, S.; Gomes, P.; Coimbra, M.; Patterson, J.D.; Langille, J.; Perez, G.; Fasken, L.
Abstract: Background: Auscultation of heart and lung sounds is a foundational competency for Registered Nurses (RNs). Precise and timely assessments are important for the early detection and recognition of the deteriorating patient. Studies have shown that improved teaching methods that incorporate emerging technologies and address different learning styles are needed to improve competency in auscultation. Method: Undergraduate nursing students ( n = 127) were randomized into treatment and control groups. The control group received the usual preparation in auscultation learning strategies. The treatment group received the usual training plus three auscultation learning sessions that were each 2 h in length (cardiac, pulmonary and mixed sounds). Results: The virtual auscultation teaching strategy had a significant impact on undergraduate nursing student's competency in recognizing heart murmurs. The treatment group also had increased scores compared to the control group increased scores in distinguishing normal versus abnormal heart and lung sounds, identification of crackles and diminished breath sounds. Conclusion: Virtual auscultation as a teaching strategy was shown to have a positive impact on undergraduate student nurse competence in accurately identifying heart and lung sounds. Highlights: Virtual auscultation as a teaching strategy had a significant impact on increasing competence in cardiac murmur recognition. Undergraduate nursing students can benefit from learning auscultation skills in a virtual learning environment. Virtual auscultation software (actual human sounds) versus synthetically created sounds have greater learning impact.